2015
DOI: 10.1093/gji/ggv060
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the mantle lithosphere of the Precambrian Grenville Province: large-scale electrical resistivity structures

Abstract: S U M M A R YThe resistivity structure of the lithospheric mantle beneath the Proterozoic Grenville Province in southern Ontario, Canada is investigated using 84 magnetotelluric (MT) sites divided into four profiles. Depth-based regional geoelectric dimensionality analyses of the MT responses indicate that the mantle lithosphere north of Lake Ontario can be subdivided into upper (45-150 km) and deeper (>200 km) lithospheric mantle layers with regional strike azimuths of N85 • E (±5 • ) and N65 • E (±5 • ), res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 92 publications
0
25
0
Order By: Relevance
“…This conductive anomaly is attributed to lithospheric refertilization by fluids associated with kimberlite fields magmatism. Additionally, a subvertical conductor located 50 km along strike from the Mesozoic Kirkland Lake and Cobalt kimberlite fields is interpreted as refertilization of an old mantle scar [Adetunji et al, 2014[Adetunji et al, , 2015. Thus, there is substantial evidence for kimberlite intrusions at the proximity of our study region.…”
Section: Kimberlite Intrusionsmentioning
confidence: 82%
See 2 more Smart Citations
“…This conductive anomaly is attributed to lithospheric refertilization by fluids associated with kimberlite fields magmatism. Additionally, a subvertical conductor located 50 km along strike from the Mesozoic Kirkland Lake and Cobalt kimberlite fields is interpreted as refertilization of an old mantle scar [Adetunji et al, 2014[Adetunji et al, , 2015. Thus, there is substantial evidence for kimberlite intrusions at the proximity of our study region.…”
Section: Kimberlite Intrusionsmentioning
confidence: 82%
“…Further North along the Great Meteor hot spot track, numerous kimberlitic melts have intruded the Canadian Slave Craton from deep within the lithosphere to the surface, over the last 500 Ma [Selway, 2014]. An MT study performed at the Grenville Province in southern Ontario, Canada, identified a conductive anomaly in the lower lithosphere that is spatially associated with low seismic velocities [Adetunji et al, 2015]. This conductive anomaly is attributed to lithospheric refertilization by fluids associated with kimberlite fields magmatism.…”
Section: Kimberlite Intrusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, the anisotropy interpretation would share the fate of another case study: Perhaps the most widely known example of lithospheric anisotropy is that seen in the Superior and Grenville Provinces of eastern Canada by Mareschal et al (1995), which was compared to seismic anisotropy across the Grenville Front by Ji et al (1996). However, a recent re-examination of data from the region by Adetunji et al (2015) concluded that the spatially homogeneous anisotropy observed in the region of the Grenville Front is consistent with isotropic 2D structures.…”
Section: The Caledonides and The Precambrian Craton: Tectonic Bordersmentioning
confidence: 97%
“…More recently, Adetunji et al . [, ] show that the MT responses in the Grenville Front area can be accurately modeled by two‐dimensional (2‐D) models without any anisotropy. As with the earlier results, these 2‐D models indicate the presence of resistive mantle lithosphere between 50 km and 150 km depth in the Grenville Province.…”
Section: Introductionmentioning
confidence: 99%